Strengthening ASEAN Centrality in the Indo-Pacific Economic Integration Through RCEP - Safitriyani Safitriyani (Dinasti Publisher, 2025)
This article examines ASEAN’s role in strengthening its centrality in Indo-Pacific economic integration through leadership in the Regional Comprehensive Economic Partnership (RCEP). Amid intensifying geopolitical competition and shifting material power in the region, ASEAN seeks to maintain its central role as a regional architect through the principle of “ASEAN Centrality.” The study explores ASEAN's functions as a regional leader, convener, driver, hub, and platform in the negotiation and formation of RCEP, the world’s largest free trade agreement by GDP and population. Employing a qualitative method with a deductive approach, the article applies the analytical framework developed by See Seng Tan (2017) to evaluate ASEAN’s five core roles within regional architecture. Findings reveal ASEAN’s effectiveness in initiating and steering multilateral economic integration, thereby enhancing its institutional relevance and its capacity to align diverse interests of major and middle powers in the region. The study underscores ASEAN’s leadership in fostering inclusive regional cooperation while safeguarding non-interference and consensus-building principles.